Aphrodisiac Activity of Ethanolic Extracts from the Fruits of Three Pepper Plants from Piperaceae Family - Idha Kusumawati; Syailendra Mahatmaputra; Rohman Hadi; Rohmania Rohmania; Subhan Rullyansyah; Helmy Yusuf; Abdul Rahman (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2021)
Background: Pepper plants belong to the Piperaceae family with many pharmacological activities. The fruits of these plants have been widely used traditionally for various therapies, one of which is an aphrodisiac. Objective: The purpose of this study was to determine the aphrodisiac activity of the fruits of three pepper plants, Piper nigrum, Piper retrofractum, and Piper cubeba to prove their traditional use. Methods: The level of piperin, the active compound of plants from the family Piperaceae, was also determined in the ethanolic extract of those three fruits of the pepper plant. The aphrodisiac activity was determined by counting the number of introducing and mounting mice. The acute toxicity test of the extract was carried out according to the OECD-423 guidelines. Results: The ethanolic extract of Piper nigrum fruits had the highest piperin concentration, while the ethanolic extract of Piper retrofractum fruits had the highest aphrodisiac activity, according to the findings. During the entire duration of the acute toxicity study, no signs of toxicity or mortality were discovered.Conclusion: This study proves that all fruits of three species of pepper plants exhibit aphrodisiac activity. Furthermore, this study also shows that not only piperin is responsible for the aphrodisiac effect.